Unidades evaporíticas Carboníferas do depósito de Potassífero de Autazes, região Ocidental da bacia do Amazonas: análises estratigráficas de sequências , geoquímicas, mineralógicas e paleoambientais - Gustavo Kiefer Lage Sousa (2019)
The western region of the Amazon Basin harbor units of Permo-Carboniferous evaporite rocks, belonging to the Nova Olinda Formation, which hosts important occurrences of potash mineralization. The proposed models for the regional tectonic and paleoenvironmental evolution of the basin consider that the wide deposition of the set of chemical and evaporite sediments of the Nova Olinda Formation of the Tapajós Group would be the result of the continental restriction phases of the basin. In the vicinity of the Autazes city, Amazonas, between the yers of 2008 and 2014, an exploration mineral campaign was conducted by the company Potássio do Brasil Ltda., Which resulted in the discovery of the Autazes Potash Deposit. The unpublished results of the petrographic, geochemical and mineralogical characterizations, as well as the regional faciological variations of the mineralized section in Autazes, indicate for controls associated with the precipitation sequence of the evaporite salts, along with the secondary pervasive diagenetic alterations. Such characterizations have allowed broader approaches, from the depositional perspectives of the mixed carbonate-evaporite settings, in the light of the Sequence Stratigraphy concepts. In these interpretations, it was considered that, among the two main depositional styles of plate scaling environments, associated with the Phanerozoic saline giants, namely: marine-platform evaporites; and basinwide evaporites, only the first would allow an eustatic marine interpretation, in line with fluctuations in sealevels. Based on these concepts, and in the depositional and erosional conditions susceptible to occur in the icehouse stages, operating in the Amazon Basin in the transition of the Carboniferous and Permian periods, a stratigraphic sequence model was proposed for the sedimentary section evaluated in the Autazes area. Two depositional sequences were thus defined, S1 and S2, associated to the phases of hydrographic isolation and partial or effective connection with the open ocean during the paleogeographic evolution of an epicontinetal sea that would have covered large areas of the intracratonic basin. In these sequences, the highstand system tracts are represented by the platform marine carbonates facies, while those of lowstand system tracs, defined by the evaporitic facies associated to the periods of hydrographic isolation of the basin. Three climate-related intrabasinal autocyclic sequences were also proposed: S2-1, S2-2 and S2-3, associated with the compositions of the lowstand evaporitic units of the S2 sequence. The stratigraphic position of the Autazes potash mineralization would thus correspond to the sylvinite facies of the Sequence S2-2. These subdivisions would be related to internal base level fluctuations inside the basin, determined by intrabasinal autocyclic controls, in association with semi-arid to arid climatic systems.